Premature Death Rates in the United States: Projections through 2030 - Best, Ana F. (Lancet Public Health, 2018)
BACKGROUND: Trends in U.S. premature mortality rates have diverged among demographic groups. METHODS: Death certificate data for the U.S. population ages 25–64 years,1990–2016, were obtained from the Centers for Disease Control and Prevention. Age-standardized premature mortality rates (ASRs) and corresponding annual percent changes (APCs) for 2017–2030 by sex and race/ethnicity were estimated using age-period-cohort forecasting models. Absolute death counts were estimated using corresponding population projections. FINDINGS: During 2017–2030, all-cause death rates are projected to increase among white women and American Indian/Alaska Natives (AIANs), resulting in 239,700 excess deaths, an 10.1% increase. Mortality declines in other groups will result in 945,900 fewer deaths (13.7% reduction). Cancer death rates are generally projected to decline, with the largest declines among black women (APC=−2∙05%/year to ASR=77∙1/100,000 in 2030) and men (−2∙64%/year; 81∙6/100,000). Heart disease death rates are projected to increase in AIAN women (+0∙52%/year; 62∙8/100,000) and men (+1∙41%/year; 175∙9/100,000) and decline in other groups. Accidental death rates are projected to increase in all groups other than API women and most rapidly among white women (+3∙71%/year; 60∙5/100,000) and men (+2∙09%/year; 101∙9/100,000), and AIAN men (+3∙08%/year; 298∙7/100,000). Suicide rates are projected to increase for all groups, and chronic liver disease/cirrhosis death rates for all but black men. A 2%/year reduction in projected accidental death rates would eliminate an estimated 178,700 deaths during 2017–2030. INTERPRETATION: To reduce future premature mortality, effective interventions are needed to address rapidly rising death rates due to accidents, suicides and chronic liver disease/cirrhosis.